2020
DOI: 10.3389/fcell.2020.591883
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Functional Neurons After Spinal Cord Injury via in situ NeuroD1-Mediated Astrocyte-to-Neuron Conversion

Abstract: Spinal cord injury (SCI) often leads to impaired motor and sensory functions, partially because the injury-induced neuronal loss cannot be easily replenished through endogenous mechanisms. In vivo neuronal reprogramming has emerged as a novel technology to regenerate neurons from endogenous glial cells by forced expression of neurogenic transcription factors. We have previously demonstrated successful astrocyte-to-neuron conversion in mouse brains with injury or Alzheimer's disease by overexpressing a single n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 62 publications
2
73
0
Order By: Relevance
“…investigation. NeuroD1 overexpression has shown promises in regenerative therapy following spinal cord injury and sciatic nerve injuries (Puls et al, 2020;Lai et al, 2020). Given that NeuroD1 partners with other bHLH TFs, discovering such partner TFs may increase success in efforts towards regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…investigation. NeuroD1 overexpression has shown promises in regenerative therapy following spinal cord injury and sciatic nerve injuries (Puls et al, 2020;Lai et al, 2020). Given that NeuroD1 partners with other bHLH TFs, discovering such partner TFs may increase success in efforts towards regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased Notch signaling due to stroke was shown to be necessary for astrocyte neurogenesis (Magnusson et al, 2014 ). The transcription factors NeuroD1, SOX2, and ZFP521 can all be used to reprogram astrocytes into neurons or neural stem cells after SCI (Zarei-Kheirabadi et al, 2019a ; Puls et al, 2020 ).…”
Section: Strategies For Astrocyte-targeted Therapymentioning
confidence: 99%
“…A complementary intriguing option that is recently coming to the spotlight is to restore lost functions by exploiting the potential of the astrocytes to trans-differentiate into neurons. In particular, it has been shown that forced expression of selected transcription factors can transform astrocytes into glutamatergic [240][241][242][243][244], GABAergic [243,245,246], dopaminergic [247], retinal [248,249], and motor neurons [250] in mice. Intriguingly, astrocyte trans-differentiation into neurons can be achieved also by downregulating the expression of the polypyrimidine tract binding protein 1 gene (Ptbp1) by either a short hairpin RNA [251] or by expression of an ortholog of CRISPR-Cas13d (CasRx) and two suitable guide RNAs [252].…”
Section: Astrocyte Role In Adult Neurogenesis and As Neuronal Precursorsmentioning
confidence: 99%